Increased Oxygen Desaturation Time During Sleep Is a Risk Factor for NASH in Patients With Obstructive Sleep Apnea: A Prospective Cohort Study - Landete, Pedro; Fernández-García, Carlos Ernesto; Aldave-Orzaiz, Beatriz; Hernández-Olivo, Marta; Acosta-Gutiérrez, Carmen M.; Zamora-García, Enrique; Ancochea, Julio; González-Rodríguez, Águeda; García-Monzón, Carmelo (Frontiers in Medicine, 2022)
Introduction Given that obstructive sleep apnea (OSA) is commonly associated with metabolic disorders, in this prospective study, we sought to determine the prevalence and risk factors for hepatosteatosis, non-alcoholic steatohepatitis (NASH), and advanced liver fibrosis in patients with clinical and polygraphic criteria of OSA (n = 153) and in subjects with normal lung function parameters (NLP, n = 43). Methods Hepatosteatosis, NASH, and advanced liver fibrosis were determined by blood-based non-invasive tools, such as the fatty liver index and the hepatic steatosis index, a serum lipidomic (OWLiver™) test, and three distinct fibrosis algorithms, respectively. Logistic regression models adjusted by potential confounders were performed to evaluate risk factors. Results Insulin resistance and dyslipidemia were more frequent in patients with OSA than in subjects with NLP. The prevalence of hepatosteatosis was significantly higher in patients with OSA than in subjects with NLP. NASH was also found more frequently in patients with OSA than in subjects with NLP. In contrast, advanced liver fibrosis was rarely detected in the entire study population, and no significant differences were observed between patients with OSA and subjects with NLP. Besides male gender, increased body mass index (BMI), and presence of type 2 diabetes, percentage of sleep time with oxygen saturation <90% (Tc90%) was the only polygraphic variable significantly associated with NASH in patients with OSA. Conclusions This study shows that hepatosteatosis and NASH are highly prevalent in patients with OSA and indicates that those with a Tc90% higher than 10% are at increased risk for NASH.